2002
DOI: 10.1146/annurev.immunol.20.100301.064753
|View full text |Cite
|
Sign up to set email alerts
|

RANK-L and RANK: T Cells, Bone Loss, and Mammalian Evolution

Abstract: TNF and TNFR family proteins play important roles in the control of cell death, proliferation, autoimmunity, the function of immune cells, or the organogenesis of lymphoid organs. Recently, novel members of this large family have been identified that have critical functions in immunity and that couple lymphoid cells with other organ systems such as bone morphogenesis and mammary gland formation in pregnancy. The TNF-family molecule RANK-L (RANK-L, TRANCE, ODF) and its receptor RANK are key regulators of bone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
651
1
12

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 730 publications
(683 citation statements)
references
References 132 publications
(189 reference statements)
11
651
1
12
Order By: Relevance
“…We observed an increment of transduction signals (RANK and RANK-L) associated both to osteoclast activation, bone remodelling, and inflammatory cell communications [20]. However, since induction of an angiogenic phenotype has been reported to be associated with the up-regulation of RANK/RANK-L signalling [21,22], conceivably this latter event might be related to a functional recovery of injured cells.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We observed an increment of transduction signals (RANK and RANK-L) associated both to osteoclast activation, bone remodelling, and inflammatory cell communications [20]. However, since induction of an angiogenic phenotype has been reported to be associated with the up-regulation of RANK/RANK-L signalling [21,22], conceivably this latter event might be related to a functional recovery of injured cells.…”
Section: Discussionmentioning
confidence: 67%
“…1). RANK (receptor activator of NK-kB) and RANK-L, biochemical markers of bone remodelling and inflammatory reactions [20], were overexpressed in hypogravity condition (Fig. 1).…”
Section: Simulated Hypogravity Alters Gene Expression Pattern In Endomentioning
confidence: 97%
“…3 OCs are multinucleated cells that are derived from hematopoietic precursors of the monocyte/macrophage lineage in the presence of macrophage colony-stimulating factor (M-CSF) and RANKL. [4][5][6][7] Many other cytokines have been shown to affect bone metabolism and OC activity, including interleukin (IL)-1, IL-4, IL-7, IL-10, IL-13 and TNF. [8][9][10] A previous study by our lab showed that both transforming growth factor-beta 1 (TGF-b1) and IL-10 suppress osteoclastogenesis and bone resorption in a dosage-dependent manner and exhibit synergistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…(1,2) The imbalance between osteoblast and osteoclast activity underlies various bone and joint diseases, such as osteoporosis and rheumatoid arthritis. (3)(4)(5)(6) Osteoclasts are multinucleated giant cells that are polarized and resorb bone through specialized machinery so as to attach to mineralized matrix and degrade it. The differentiation of monocyte/ macrophage-lineage precursor cells into mature osteoclasts is induced by the tumor necrosis factor (TNF) family cytokine receptor activator of NF-kB ligand (RANKL) together with colonystimulating factor (M-CSF), and provides an activating signal as well as survival signals to osteoclasts.…”
Section: Introductionmentioning
confidence: 99%